Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Smartphone Merek Realme Di Kecamatan Batukliang Kabupaten Lombok Tengah - Rizky Tri Septiawan; Junaidi Sagir; Rusminah HS (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2023)
This research is entitled the influence of product quality and price of realme brand smartphones on purchasing decisions (studies in Batuliang sub-district, Central Lombok district). The aim is to determine the effect of product quality and price on purchasing decisions. The type of research used is quantitative with an associative approach. The data collection method used is the purposive sampling. The population and respondents in the study were 60 people in Batukliang District, Central Lombok Regency. The analytical tool used is Multiple Linear Regression using SPSS version 25. The results of the analysis show that: (1) the quality of Realme brand smartphone products has a positive and not significant effect on purchasing decisions (2) The price of Realme brand smartphone products has a positive and significant effect on purchasing decisions.